2021
DOI: 10.3389/fpsyg.2021.628004
|View full text |Cite
|
Sign up to set email alerts
|

Examining Approach and Avoidance Valences of the 3 X 2 Achievement Goal Types on an Engineering Student Sample: A Validity Approach

Abstract: Development of the 3 × 2 achievement goal questionnaire (AGQ) advanced approach and avoidance goals in three goal types within the achievement goal framework: task-, self-, and other-based. The purpose of the present study was to examine empirical support for the construct validity, reliability, and measurement invariance of factors on the questionnaire and compare model fit of the 3 × 2 configuration to other alternatives. In addition to validating some of the findings reported in earlier studies, especially … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 54 publications
(115 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, correlation and regression analyses were conducted using participants' final achievement scores as an outcome variable and self‐efficacy, task value, and achievement goals as predictors. The mastery‐avoidance construct has been criticized by multiple authors because it is often very highly correlated with—and thus empirically indistinguishable from—mastery‐approach goal (Hunsu et al, 2021; Johnson & Kestler, 2013; Lower & Turner, 2016). Similarly, other studies have found no statistically significant relationship between mastery‐avoidance goal and student achievement.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…Subsequently, correlation and regression analyses were conducted using participants' final achievement scores as an outcome variable and self‐efficacy, task value, and achievement goals as predictors. The mastery‐avoidance construct has been criticized by multiple authors because it is often very highly correlated with—and thus empirically indistinguishable from—mastery‐approach goal (Hunsu et al, 2021; Johnson & Kestler, 2013; Lower & Turner, 2016). Similarly, other studies have found no statistically significant relationship between mastery‐avoidance goal and student achievement.…”
Section: Data Analysis and Resultsmentioning
confidence: 99%
“…The self-approach goal and the self-avoidance goal motivate students to pursue performing better than and to avoid not performing worse than what they have done in the past, respectively. The other-approach goal and the other-avoidance goal urge students to outperform and avoid not performing worse than others, respectively ( Hunsu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have favored the 3 × 2 achievement goal model across countries and subject domains ( Wu, 2014 ; Gillet et al, 2015 ; Hoi, 2016 ; Mascret et al, 2017 ; Méndez-Giménez et al, 2017 , 2018 ; Wang et al, 2017 ; Hidayat et al, 2018 ; Danthony et al, 2020 ; Hunsu et al, 2021 ). However, this model has mainly been applied to school-aged samples, the exception being Wu (2022b) , who developed an instrument to measure kindergarteners’ achievement goals based on the 3 × 2 achievement goal framework, and this model as preliminarily demonstrated to be the best theoretical model for understanding kindergarteners’ achievement goals.…”
Section: Introductionmentioning
confidence: 99%
“…They include mastery‐approach goals, focused on attaining task‐based or self‐based competence; mastery‐avoidance goals, focused on avoiding task‐based or self‐based incompetence; performance‐approach goals focused on attaining other‐based competence; and performance‐avoidance goals, focused on avoiding other‐based incompetence (Elliot et al, 2011). Nathaniel Hunsu tested the 3 × 2 achievement goal model based on an engineering student sample, examining the approach and avoidance valences of the 3 × 2 achievement goal types and discussing the limitations and potential boundaries of the 3 × 2 achievement goal questionnaire (Hunsu et al, 2021). Many scholars have conducted empirical studies using the 3 × 2 achievement goal framework.…”
Section: Introductionmentioning
confidence: 99%